The Fifth Evaluation Report on Working of Community Development and N.E.S. Blocks Summary and Conclusions - Planning Commission (Planning Commission, 1958)
This is the fifth Evaluation Report. It is based upon four elabo rate field enquiries into the organisation and operation of the com munity development and the N.E.S. programmes, the organisation and working of the panchayats, the dissemination of improved agricul tural practices and the growth of people’s participation and, finally, the maintenance of records in the development blocks. The emphasis has been on a relatively intensive study of a few selected topics rather than an extensive review of all aspects of the programme. What the study may have lost in comprehensiveness, it has, it is hoped, gained+M17 in depth. To the reader, the data and the analysis should be as important as the conclusions reached.
Programme Evaluation Organisation Planning Commission